Difficulties of applying e-learning in teaching chemistry to high school students from the point of view of supervisors, teachers, and students in Nalut, Libya - Al-Sifaw, Saeed Ahmed Saeed; Abdullah, Abdul Hakim (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the difficulties that hinder the implementation of e-learning. This study used the descriptive design using the quantitative approach by using a questionnaire as a study tool after confirming its degree of validity and reliability. The random sample that was (724) chosen among supervisors, teachers and students from the Libyan high school Nalut, for the academic year 2018-2019. Descriptive analysis was done using the statistical analysis SPSS version (21.0). One of the most prominent results of this study was that the difficulties of the contexts came in the first order with an arithmetic average (3.79), while the technological difficulties in the second order with an arithmetic average (3.77), while the individual difficulties in the third arrangement with an arithmetic average (3.75), and finally the difficulties of the curriculum in the ranking Fourth, with an average of (3.62). And all the difficulty level was high, as the total areas of the tool got an arithmetic average (3.73), and this indicates that the level of difficulties that prevent the application of e-learning in teaching chemistry to high school students from the point of view of supervisors, teachers and students is high. The study suggested a conceptual framework that integrates the difficulties and the relationship with the individual’s difficulties, and the proposed conceptual framework contributes to knowing the obstacles of e-learning by creating a guide for educational institutions in Libya in order to develop and implement better, and it works as a tool to avoid the failure of implementing new e-learning projects through planning that meets trends and tendencies Individuals toward the effective use of e-learning and as an evaluation method for the effectiveness of existing e-learning projects.